2020
DOI: 10.1002/asia.202001157
|View full text |Cite
|
Sign up to set email alerts
|

Design Principles of Interfacial Dynamic Bonds in Self‐Healing Materials: What are the Parameters?

Abstract: Polymers and polymer nanocomposites (PNCs) are extensively used in daily life. However, the growing requirement of advanced PNCs laid persistent environmental issues due to deformation‐induced damage that once formed, does not vanish at future stages. Therefore, self‐healing materials with significantly enhanced long life and safety have been designed to epitomize the forefront of recent advances in materials chemistry and engineering. Self‐healing PNC (SH‐PNCs) materials are a class of smart composites in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 252 publications
(238 reference statements)
1
10
0
Order By: Relevance
“…This trend was also observed by Wang et al The lower tan δ of WSR indicated high filler–filler interaction with low filler–rubber interaction . However, the filler–rubber interaction can be improved by using an interfacial modifier. , …”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…This trend was also observed by Wang et al The lower tan δ of WSR indicated high filler–filler interaction with low filler–rubber interaction . However, the filler–rubber interaction can be improved by using an interfacial modifier. , …”
Section: Resultssupporting
confidence: 74%
“…Reinforcing fillers have been developed for rubber composite products to improve their quality characteristics such as the modulus, tensile strength, and abrasion resistance and are critical to practical rubber technology. Nowadays, the amount of the silica (SiO 2 ) filler used as an additive in the tire industry is continuously increasing because silica-reinforced rubber presents a low rolling resistance, low hysteresis, high hardness, and good abrasion resistance, and they are technical advantages over carbon black-filled rubber. , In addition, the improvement of the self-healing capability of the silica-filled rubber composite for extending its long life and safety was studied by several investigators. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although understanding of the effects of filler NPs on a polymer matrix is crucial at the molecular level, [77–84] because of the limited laboratory techniques with a low‐resolution limit (1 to 100 nm), the atomistic physics behind the observed phenomena has remained unclear (Harding et al., 2008) [85] . Hence, the use of computational methods has developed progressively to realize materials assembly and performance (Heinz et al.,2016; Gunsteren et al., 2006; Heinz et al., 2013; and Huang et al., 2011) [20,86–88] .…”
Section: Polymer‐filler Interfacial Interactions In Pncs: What Are the Parameters?mentioning
confidence: 99%
“…Dynamic interactions, including supramolecular interactions and dynamic covalent bonds (DCBs), can reversibly break down and build up, and well respond to external stimuli. Recently, dynamic interactions have been introduced into the polymer and endow the polymer with various advanced properties, such as self-healing, shape memory, adaptability, and stimuli-responsiveness [ 4 , 5 , 6 ]. Generally, there is a compromise between mechanical performance and dynamic behavior when dynamic interactions are introduced into the polymeric materials.…”
Section: Introductionmentioning
confidence: 99%